Analysis of online traffic campaigns for selling a politics segment info-product - Oliveira, Lucas Patrick Gonçalves; Souza, Neuber Samy Ferreira de; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2024)
With the evolution of technologies and the intensification of market globalization, companies have needed to adopt innovative marketing approaches to ensure their competitiveness. Digital marketing has emerged as a crucial area for the development of these strategies. One of the fundamental tools of digital marketing is the use of paid traffic, which provides effective brand consolidation and a broader reach. This study was conducted in a digital marketing agency with the aim of analyzing the impact of paid traffic campaigns on the sales of an info-product. The methodology adopted was based on a case study, which included a theoretical review of marketing as well as a detailed analysis of the data from the company's campaigns. Additionally, all digital marketing strategies employed were thoroughly characterized. At the end of the research, the data obtained highlighted the positive results achieved by the company through the implementation of digital marketing. Furthermore, improvements were proposed to enhance the results obtained. Thus, this study contributed to the understanding of the importance of digital marketing and paid traffic on social media platforms in boosting the sales of an info-product.
Keywords: Digital Marketing; Paid Traffic; Info-product